PENCAPAIAN KEPUASAN KERJA BAGI KARYAWAN MELALUI KONDUSIVITAS LINGKUNGAN KERJA DAN MOTIVASI KERJA - Samsul Arifin; Rahayu Mardikaningsih (Jurnal Ilmiah Satyagraha, 2022)
Employees are the company's capital to run its operations. Notonly high sales, having good employees and having high abilities will helpthe company to achieve company goals. The importance of employees forcompanies requires management to always satisfy employees while working.Factors that can increase job satisfaction will always be the attention ofmanagement such as the work environment and work motivation. This studyaims to determine and analyze the role of work environment and workmotivation on job satisfaction. This research was conducted at one of thecompanies in Sidoarjo. This study used 92 respondents as a sample. Theanalytical technique used was multiple linear regression. The results showedthat the work environment had a significant effect on building jobsatisfaction. Work motivation has also been shown to have a significant effecton the formation of job satisfaction. Both variables have a significant effecton increasing job satisfaction.